Concrete sustainable buildings using domestic wastewater treated - Verde, Sharlys (2022)
During recent years, the rapid growth of the population in urban areas has promoted the development of housing, roads, shopping centres and industries; having increased the consumption of tap water in the concrete industry. A solution to this problem, is to use domestic wastewater treated, due to the large quantities produced and the need to include them within the life cycle of the water; thus bridging the gap of service in urban and rural areas. The present research seeks to use the domestic wastewater treated in the production of concrete for construction; the results show slightly for the slump, initial setting time and splitting tensile increase, and that the resistance to compression and flexural is decreased.